2021
DOI: 10.1177/00031348211048841
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 Intestinal and Mesenteric Mucormycosis

Abstract: A thirty-eight-year-old uncontrolled diabetic with a recent COVID-19 infection presented with extensive bowel ischemia and gangrene with a microscopic diagnosis of intestinal and mesenteric mucormycosis. Although there are a few reported cases of primary gastrointestinal mucormycosis, our case showing involvement of the intestine and/or mesentery, that too in a post-COVID patient, is quite uncommon. The immunosuppressive effect of the COVID-19 disease, uncontrolled diabetes, and the use of corticosteroids for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Conditions like hemochromatosis and the use of iron chelators such as deferoxamine elevate the risk of mucormycosis. Our patient had poorly controlled blood sugar levels, and was pretreated with corticosteroids before manifesting symptoms of cutaneous mucormycosis [7]. As reported by Song G et al, severely ill COVID-19 patients who require prolonged hospitalization, admission to the intensive care unit (ICU), or invasive mechanical ventilation are particularly vulnerable to invasive mycoses [16].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Conditions like hemochromatosis and the use of iron chelators such as deferoxamine elevate the risk of mucormycosis. Our patient had poorly controlled blood sugar levels, and was pretreated with corticosteroids before manifesting symptoms of cutaneous mucormycosis [7]. As reported by Song G et al, severely ill COVID-19 patients who require prolonged hospitalization, admission to the intensive care unit (ICU), or invasive mechanical ventilation are particularly vulnerable to invasive mycoses [16].…”
Section: Discussionmentioning
confidence: 61%
“…There is evidence of a rising number of cases among patients who have successfully recovered from initial COVID-19 infection, with the vast majority originating in the subcontinent region [6]. Patients may have an increased susceptibility to CAM due to their compromised immune status, which can result from the viral infection itself, previous corticosteroid therapy, or uncontrolled blood sugar levels [7]. Studies have indicated that the median duration for the development of mucormycosis is approximately 10 to 15 days following a COVID-19 diagnosis [8].…”
Section: Introductionmentioning
confidence: 99%